On discreteness of spectrum of a second order differential operator - Labovskiy Sergey M. (Electronic journal of qualitative theory of differential equations, 2020)
A new form of a necessary and sufficient conditions for the discreteness of the spectrum of singular operator − 1 ρ(x) (p(x)u 0 0 , −∞ ≤ a ≤ x ≤ b ≤ +∞ is obtained. A simpler proof of the necessity is obtained.